2021
DOI: 10.1111/bcp.14890
|View full text |Cite
|
Sign up to set email alerts
|

Public availability of results of ClinicalTrials.gov‐registered expanded access studies

Abstract: Funding information Kosciuszko FoundationAims: Expanded access is the use of investigational treatments outside of clinical trials. Results of expanded access studies provide insights into how investigational treatments work in real-world settings. The objective of this study was to evaluate public availability of results of expanded access studies. Methods: Eligible expanded access studies were identified in ClinicalTrials.gov (CT. gov). Publications matching records of individual studies were searched for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In fact, our recent study showed that after a median time of 49.5 months from study completion, the results of only 45.39% of ClinicalTrials.gov-registered expanded access studies were publically available. 31 Therefore, our results may not reflect the actual scale of the problem of COIs in programs providing access to anticancer treatments outside of clinical trials. However, there is no comprehensive source of data enabling one to examine COIs in oncology expanded access studies.…”
Section: Discussionmentioning
confidence: 85%
“…In fact, our recent study showed that after a median time of 49.5 months from study completion, the results of only 45.39% of ClinicalTrials.gov-registered expanded access studies were publically available. 31 Therefore, our results may not reflect the actual scale of the problem of COIs in programs providing access to anticancer treatments outside of clinical trials. However, there is no comprehensive source of data enabling one to examine COIs in oncology expanded access studies.…”
Section: Discussionmentioning
confidence: 85%